Integration of Character Values and Religious Moderation in School Activities at SMP Negeri 1 Yogyakarta - Syachputri, Lendy Fathmi Lia; Achadi, Muhammad Wasith (UMSU, 2025)
This study aims to describe how character values and religious moderation are integrated into school activities at SMP Negeri 1 Yogyakarta. The research method used is a qualitative approach with a descriptive research type. Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results indicate that the integration of character values and religious moderation is carried out through habituation, teacher role models, cross-student religious activities, and a school culture that emphasizes tolerance and discipline. In conclusion, the integration of these values is effective because it is supported by a religious and inclusive school culture and the role of Islamic Religious Education teachers as role models and prime movers. These findings confirm that strengthening character and religious moderation can be achieved sustainably if all school members actively participate in building a tolerant, disciplined, and socially empathetic environment.